Transforming Global Health Partnerships Critical Reflections and Visions of Equity at the Research-Practice Interface - Stewart Ibarra, Anna.; LaBeaud, A. Desiree; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
This is a book about the human experience of doing infectious disease research, linked to operational responses to disease outbreaks around the world. Rather than a manual or how-to guide, this book presents a roadmap and vision for equitable, sustainable, and impactful partnerships shared through a rich interweaving of voices -- north and south, academics and community practitioners, senior mentors and trainees, multiple generations, multiple disciplines. It focuses on the stories that need to be told, the successes and the failures, and visions for a healthier and more compassionate future for humanity. Each of the book's three sections address a key dimension of infectious disease work now and in the future. Section I provides background on the foundational principles of the field, and critically examines the successes and shortcomings of current structures. Section II presents case studies from a diverse collection of authors acrossresearch, academia, policy, and practice, highlighting both unique and shared experiences. The final section proposes sustainable, equitable improvements, within the context of a changing global landscape and the future of pandemics and infectious disease research. This is an open access book.
1. Prologue -- 2. Colonialism, decolonization, and global health -- 3. Ethical challenges in global health research -- 4. Gender equity in African academia: An implementation science evaluation of the Kenya context -- 5. A holistic systems approach to global health research, practice, and partnerships -- 6. Team science and infectious disease work: Exploring opportunities and challenges -- 7. Foundations and future directions of global health communication -- 8. Collective learning: Power and trust in partnerships -- 9. Partnering with the community in infectious disease research: A Kenyan experience -- 10. Partnership-based approach to infectious disease research in Papua New Guinea -- 11. Partnerships to improving access to healthcare for refugees and immigrants in Philadelphia -- 12. The strengths and challenges of building partnerships through malaria research: Thailand case study in inter-epidemic and epidemic projects -- 13. Building partnerships and confronting challenges: Implementation ofan Ebola vaccine clinical study during an outbreak in the Democratic Republic of the Congo -- 14. Innovative, collaborative approaches that improve responses to epidemics and natural disasters -- 15. Nipah outbreak investigation in Bangladesh, 2007: A case study of One Health partnership and intersectoral coordination -- 16. Addressing sexual and HIV-related stigma in Haiti: Need for societal engagement -- 17. Building partnerships to empower women through home self-sampling for sexual and reproductive tract infections -- 18. Perspectives on community-based participatory research: An approach for more inclusive research -- 19. Gender equality in academia: Thriving as a clinician-scientist, establishing partnerships, and driving policy for change in the Kenya context -- 20. Transforming the planetary health crisis through an Indigenous Land-based meta narrative -- 21. Social movement and empowerment in shaping global health priorities: Past, present, and future -- 22. When women lead in globalhealth: Alternative mobilizations -- 23. Funding for equitable infectious disease research and development -- 24. Educational perspectives from the field: Pathways to the future -- 25. Learning from the past to inform the future: Perspectives on future directions in international health and research -- 26. Engaging with heart in global health partnerships -- 27. Courageous authenticity: Bringing our inner wisdom to our work, partnerships, and communities for deeper partnership.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Immunology; Medicine -- Research; Biology -- Research; Public health; Epidemiology; Medical Ethics; Immunology; Biomedical Research; Public Health; Epidemiology; Medical Ethics